2019
DOI: 10.1186/s40635-019-0250-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-controlled adaptive ventilation (TCAV) accelerates simulated mucus clearance via increased expiratory flow rate

Abstract: Background Ventilator-associated pneumonia (VAP) is the most common nosocomial infection in intensive care units. Distal airway mucus clearance has been shown to reduce VAP incidence. Studies suggest that mucus clearance is enhanced when the rate of expiratory flow is greater than inspiratory flow. The time-controlled adaptive ventilation (TCAV) protocol using the airway pressure release ventilation (APRV) mode has a significantly increased expiratory relative to inspiratory flow rate, as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A similar study found a PEFR target of 75% during T-low resulted in the least alveolar microstrain (107). In other animal models, APRV has had a favorable effect on dynamic alveolar homogeneity (108) and has also led to improved mucous clearance (109). APRV was found to reduce inflammation and pulmonary edema in a rabbit model of ARDS (110).…”
Section: Animal Modelsmentioning
confidence: 81%
“…A similar study found a PEFR target of 75% during T-low resulted in the least alveolar microstrain (107). In other animal models, APRV has had a favorable effect on dynamic alveolar homogeneity (108) and has also led to improved mucous clearance (109). APRV was found to reduce inflammation and pulmonary edema in a rabbit model of ARDS (110).…”
Section: Animal Modelsmentioning
confidence: 81%
“…In lungs with global edema, accelerated deflation also led to release of fluid from flooded alveoli, but the fluid redistributed to neighboring alveoli due to the higher surface tension, with no improvement in flooding heterogeneity (Wu et al, 2017). The importance of accelerated deflation on mucous clearance has similarly been described in a porcine lung model and represents a ventilator setting that may alter the lung micro-environment (Mahajan et al, 2019).…”
Section: Alveolar Edemamentioning
confidence: 88%
“…Indeed, our work in translational animal models and a meta-analysis of data on surgical intensive care unit (SICU) patients has shown that our time-controlled adaptive ventilation (TCAV) method, using airway pressure release ventilation (APRV) mode, is highly effective at keeping the lung open and stable, significantly reducing morbidity in translational animal models and reducing the ARDS incidence and mortality rates of SICU patients at high risk of developing ARDS (Roy et al, 2012;Andrews et al, 2013;Emr et al, 2013;Roy S.K. et al, 2013;Kollisch-Singule et al, 2014a,b, 2015aNieman et al, Nieman et al, 2015, 2017aSmith et al, 2015;Jain et al, 2016Jain et al, , 2017Satalin et al, 2018;Silva et al, 2018;Mahajan et al, 2019).…”
Section: A Physiologically Informed Strategy To Effectively Open and mentioning
confidence: 99%